Parental age and birth order in Chinese children with congenital heart disease. Issue 6 (December 1982) - Tay, J S; Yip, W C; Joseph, R
Abstract : Parental age and birth order were studied in 100 Chinese children with congenital heart disease (proven by cardiac catheterisation) and in 100 controls. A higher incidence of congenital heart disease was present in the children with higher birth orders. No relationship was found between the incidence and the paternal or maternal ages. Using the method of multiple regression analysis this birth order effect was significant (p less than 0.01) and independent of parental age. This finding provides indirect evidence of environmental influence in the causation of congenital heart disease, which is known to be inherited in a multifactorial manner. Family planning to limit the size of the family may possibly contribute to the reduction of the incidence of congenital heart disease.